1993
DOI: 10.1182/blood.v81.5.1393.1393
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for restricted Epstein-Barr virus latent gene expression and anti-EBNA antibody response in solid organ transplant recipients with posttransplant lymphoproliferative disorders

Abstract: Epstein-Barr virus (EBV) is associated with the development of two human B-cell malignancies, Burkitt's lymphoma and lymphomas that occur in the immunosuppressed host. The latter category of disease has become important recently as it is seen primarily in organ transplant recipients and individuals with acquired immunodeficiency syndrome. One possible mechanism for lymphoma development involves a reduction in or lack of EBV-specific cytotoxic T-cell recognition. In support of this model are previous observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(13 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…30,31 Although further experiments are needed to provide direct evidence, it is tempting to speculate that the lack of BSAP and Oct-2 might be the reason why type III latency with EBNA-2-6 expression is not induced in the KMH2 EBV cells. It is likely that the same condition determines the silence of Wp/Cp in other EBV-carrying lymphomas with a postgerminal center (post-GC) phenotype, such as cells in posttransplant lymphoproliferative disease (PTLD), 32,33 the rare EBV-positive plasmacytomas, 34 pleural effusion lymphomas (body cavity lymphomas) 35,36 and plasmablastic lymphomas of the oral cavity. 37 Requirement for the B-cell phenotype for type III EBV latency was first shown in experiments with somatic cell hybrids, since only those hybrids that maintained the B-cell phenotype, provided by one of the partners, maintained the type III latency.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Although further experiments are needed to provide direct evidence, it is tempting to speculate that the lack of BSAP and Oct-2 might be the reason why type III latency with EBNA-2-6 expression is not induced in the KMH2 EBV cells. It is likely that the same condition determines the silence of Wp/Cp in other EBV-carrying lymphomas with a postgerminal center (post-GC) phenotype, such as cells in posttransplant lymphoproliferative disease (PTLD), 32,33 the rare EBV-positive plasmacytomas, 34 pleural effusion lymphomas (body cavity lymphomas) 35,36 and plasmablastic lymphomas of the oral cavity. 37 Requirement for the B-cell phenotype for type III EBV latency was first shown in experiments with somatic cell hybrids, since only those hybrids that maintained the B-cell phenotype, provided by one of the partners, maintained the type III latency.…”
Section: Discussionmentioning
confidence: 99%
“…It is strongly associated with recent EBV infection. 7,10,[20][21][22][23][24][25][26] In immunosuppressed patients, PTLD is believed to result from inadequate T-cell control over EBVdriven B-cell proliferation. 2 Data from EBV in situ hybridization studies have been previously reported [22][23][24][25] , 19 of the 20 cases analyzed had positive EBV hybridization findings.…”
Section: Discussionmentioning
confidence: 99%
“…7 A particularly close association has been noted after therapy with the monoclonal antibody OKT3, 8,9 and the Epstein-Barr virus (EBV) is believed to have an important etiologic role in the development of PTLD. 7,10 The malignant lymphomas typically behave in a very aggressive fashion, with a far greater incidence of extranodal presentation and invasion of the central nervous system, a lesser likelihood of response to conventional lymphoma therapies, and poorer outcome than lymphomas in nontransplanted patients. 11 In light of these differences and the apparently greater incidence of PTLD in liver transplant recipients, we examined the clinical characteristics, course, and therapeutic outcome of PTLD in liver transplant recipients.…”
Section: Copyright 1999 By the American Association For The Study Of mentioning
confidence: 99%
“…In latent infection gene expression is greatly restricted, with a series of programs expressing 0-10 genes (Kieff & Rickinson, 2001). In NHL, expression of EBV proteins is variable, although a type III latency pattern, which includes LMP1, is common in immunodeficient patients (Cen et al, 1993;Kuze et al, 2000). Thus, LMP1 is expressed in both IM and invasive EBV-driven NHL.…”
mentioning
confidence: 99%